Do syllables play a role in German speech perception? Behavioral and electrophysiological data from primed lexical decision - Bien, Heidrun; Bölte, Jens; Zwitserlood, Pienie (Frontiers in Psychology, 2015)
We investigated the role of the syllable during speech processing in German, in an auditory-auditory fragment priming study with lexical decision and simultaneous EEG registration. Spoken fragment primes either shared segments (related) with the spoken targets or not (unrelated), and this segmental overlap either corresponded to the first syllable of the target (e.g., /teis/ - /teisti/), or not (e.g., /teis/ - /teistləs/). Similar prime conditions applied for word and pseudoword targets. Lexical decision latencies revealed facilitation due to related fragments that corresponded to the first syllable of the target (/teis/ - /teisti/) in some but not all (/teist/ - /teistləs/) conditions. Despite segmental overlap, there were no positive effects for related fragments that mismatched the first syllable. No facilitation was observed for pseudowords. The EEG analyses showed a consistent effect of relatedness, independent of syllabic match, from 200 – 500 ms, including the P350 and N400 windows. Moreover, this held for words and pseudowords alike. The only specific effect of syllabic match for related prime - target pairs was observed in the time window from 200 – 300 ms. We discuss the nature and potential origin of these effects, and their relevance for speech processing and lexical access.